Integrated power system - WADDINGTON; CLIVE (1987)
An integrated power system for use with a gas turbine engine is provided for driving and steering a tracked vehicle under the control of the vehicle's operator. The system includes a multispeed transmission for transmitting power from a free power turbine, included in the gas turbine engine, to combining planetary gear systems driving the vehicle, elements of the combining planetary gear systems also being driven by a variable displacement hydraulic steering motor. The transmission is connected to a direct displacement pump for supplying fluid under pressure to the steering motor and to an accumulator which stores and releases energy to the pump to reduce shock to the system as the speed ratio of the transmission is changed in response to the speed of the free power turbine. A control system, responsive to the vehicle's operator, determines operation of the hydraulic steering motor to effect steering as well as controlling the power output of the gas turbine engine. The control system, in response to the vehicle's operator, also controls pivot steering as well as movement of the vehicle in forward or reverse directions. An overrunning clutch interconnects the free power turbine to the gas producer whenever the turbine tries to exceed the speed of the gas producer.